Interactions of polyomavirus middle T with the SH2 domains of the pp85 subunit of phosphatidylinositol-3-kinase. - Yoakim, M (1992)
The binding of phosphatidylinositol-3-kinase to the polyomavirus middle T antigen is facilitated by tyrosine phosphorylation of middle T on residue 315. The pp85 subunit of phosphatidylinositol-3-kinase contains two SH2 domains, one in the middle of the molecule and one at the C terminus. When assayed by blotting with phosphorylated middle T, the more N-terminal SH2 domain is responsible for binding to middle T. When assayed in solution with glutathione S transferase fusions, both SH2s are capable of binding phosphorylated middle T. While both SH2 fusions can compete with intact pp85 for binding to middle T, the C-terminal SH2 is the more efficient of the two. Interaction between pp85 or its SH2 domains and middle T can be blocked by a synthetic peptide comprising the tyrosine phosphorylation sequence around middle T residue 315. Despite the fact that middle T can interact with both SH2s, these domains are not equivalent. Only the C-terminal SH2-middle T interaction was blocked by anti-SH2 antibody; the two SH2 fusions also interact with different cellular proteins.